The animal paradox: animals, sovereignty and the politics of eating - Young, Katherine E., author; MacDonald, Bradley J., advisor; Chaloupka, William J., advisor (Colorado State University. Libraries, 2008)
Looking at the history of political thought, it becomes clear that animals are the decisive political exception in Western politics. It is not that animals are simply excluded in the history of political thought, however, but that they are "inclusively excluded," demarcating the constitutive outside of politics. In other words, animals are characterized as unable to differentiate themselves from their world because they are irrational, speechless and/or appetite driven, and for these reasons, they function as markers for the state of nature and the exit point of politics. Expanding the Italian political theorist Giorgio Agamben's work on the state of exception, it appears that the sacrifice of animal bodies-not simply the idea of animality-becomes vital to sustaining key political concepts like sovereignty, democracy and rights. More specifically, there is an underlying politics of eating that nourishes the Western canon. In the simplest terms, the politics of eating is a secular transubstantiation of sovereign power, in which meat is the material good (signifying the good life) that is consumed by political subjects to mitigate the tension between individual and state sovereignty. Of course, this economy of relations is exacerbated under late capitalism. With the advent of the animal rights movement, however, animals are now drawn into this anthropological political space. Yet, because so many animal advocates (scholars and activists alike) embrace traditional understandings of rights, democracy and sovereignty, they inadvertently support juridical forms that undermine their projects. With this in mind, and given the exceptional political state of animals, it is timely to think about new political strategies that take seriously the irony of animals within the larger context of politics as well as restore the public spectacle of meat, in order to reveal and disrupt the sacrificial politics of eating, which includes both humans and animals.
Keywords: animal politics; animal rights; eating; political theory; politics; sovereignty; political science